Floor plan of Phonse Ducey's fish store, Keels, NL. - Farnham, Alicia; McDougall, Claire; Morritt, Noah (2012)
Built sometime between 1985 and 1987 Phonse Ducey’s fish store is a simple structure of red painted pressboard, with a framework of 2x4s exposed on the interior. The red paint imitates the style of older days when most fish stores were coloured with red ochre. Despite the name, Phonse’s fish store is never used to store fish; it is exclusively intended for the storage of fishing paraphernalia. Inside, are a work bench, two shelves holding large wooden puncheons, and two pounds. Pounds are generally used to store salt fish; however, these pounds hold dozens of jerry cans, wooden license tags, ropes, and nets. As in many other stores in the area, the rafter space is used for storage of long tools such as oars, jiggers, prongs, and poles.